Low‐level Laser Therapy Ameliorates CCl4‐induced Liver Cirrhosis in Rats. (18th September 2012) - Oliveira‐Junior, Manoel Carneiro; Monteiro, Aldaíza Salomão; Leal‐Junior, Ernesto César Pinto; Munin, Egberto; Osório, Rodrigo Aléxis Lazo; Ribeiro, Wellington; Vieira, Rodolfo Paula
Abstract This study investigated the effects of low‐level laser therapy (LLLT) in the liver function, structure and inflammation in a experimental model of carbon tetrachloride (CCl4)‐induced liver cirrhosis. Wistar rats were divided into Control, LLLT, CCl4 and CCl4+LLLT groups. CCl4 groups received CCl4 (0.4 g kg−1; i.p.), three times a week, for 12 weeks. A 830 nm LLLT was performed with a continuous wave, 35 mW, 2.5 J cm−2 per point, applied to four points of the liver (right and left upper and lower extremities, in the four lobes of the liver) for 2 weeks. Liver structure and inflammation (cirrhotic areas, collagen deposition, inflammation, density of Kupffer and hepatic stellate cells) and function (aspartate aminotransferase, alkaline phosphatase, gamma glutamyltransferase, lactate dehydrogenase, total proteins and globulins) were evaluated. LLLT significantly reduced CCl4‐increased aspartate aminotransferase (P < 0.001), alkaline phosphatase (P < 0.001), gamma‐glutamyl transferase (P < 0.001) and lactate dehydrogenase (P < 0.01) activity, as well as total proteins (P < 0.05) and globulins (P < 0.01). LLLT also reduced the number of cirrhotic areas, the collagen accumulation and the hepatic inflammatory infiltrate. Of note, LLLT reduced CCl4‐increased number of Kupffer cells (P < 0.05) and hepatic stellate cells (P < 0.05). We conclude that LLLT presents beneficial effects on liver function and structure in an experimental model of CCl4‐induced cirrhosis.